Pengaruh Sosial Media Co-Creation dan Praktik Akuntansi Manajerial Terhadap Keberlanjutan Industri Hospitality dengan Kinerja Perusahaan Sebagai Variabel Mediasi - Wulandari Agustiningsih; Tri Hanani; Victoria Kusumaningtyas Priyambodo; Novia Rizki (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2026)
This study examines the effect of social media co-creation integration and managerial accounting practices on the sustainability of the hospitality industry, with company performance as a mediating variable. This research uses a survey method with a purposive sampling technique conducted on the Gen Z population involved in co-creation in the hospitality industry. Social Cognitive Theory and Theory of Planned Behavior are used to understand social interactions and adoption factors. In the data collection stage, researchers managed to obtain a total of 202 questionnaires for further testing using smartpls. The results of the study show a significant relationship between social media integration and the sustainability of the hospitality industry, with company performance as a mediator. Managerial Accounting has no direct influence on Hospitality Sustainability and is not significant. This study provides strategic recommendations for stakeholders to improve performance and sustainability through technological innovation in the hospitality industry